If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4f+11=29
We move all terms to the left:
-4f+11-(29)=0
We add all the numbers together, and all the variables
-4f-18=0
We move all terms containing f to the left, all other terms to the right
-4f=18
f=18/-4
f=-4+1/2
| 3k-5=3k-1 | | 15+0.50m=25m+0.25m | | 3(k-8)-5k=k-24 | | 17=n/2+12 | | -2x-1.4=6+3x | | -2|7-3y|-6=14 | | 14x-1+18x-2=35 | | -5x-26=4x+10 | | 5(m-1)=-24 | | 4x-4(7-5x=-20 | | 4q(q+1)2(4q+5)=0 | | z−49−13=59 | | -2.06f+18=-10.84 | | ⅓(t+6)-10=-3t+2 | | 4x+19=3+7x-8 | | 4x-60=-72 | | x=1.333*(x-90000) | | 4x+3=-4+2x+15 | | 9.6x-15.4=-4.3x+26.3 | | 4x-60=72 | | 4x+19=5x+7 | | -63=7g-14g= | | x/3=8/11 | | 2-3x3=3 | | 3m+6=6m | | 4|7y+2|-8=-7 | | 6+-v/8=4/7 | | 5(2x+8)–5x=5(5x+6) | | 52+90+y=180 | | -t/13=15 | | 6(-3x+2)-6x=60 | | 5m-55=30 |